A usability study of printed pamphlets of the Agricultural Research Council (ARC) in the rural community of Ga-Matlala - Snyman, M.E. (Martha Elizabeth) (University of Pretoria, 2013)
Dissertation (MA (Development Communication))--University of Pretoria, 2008.